PROTOTYPE THEORY IN THE JUDICIAL PRACTICE OF THE COURT OF JUSTICE OF THE EUROPEAN UNION. A CASE STUDY - Zeifert, Mateusz (Comparative Legilinguistics, 2020)
Prototype theory is a semantic theory according to which the membership of conceptual categories is based not on a list of criterial features, but rather on the similarity to the most representative member of the category. Consequently, conceptual categories may lack classical definitions and rigid boundaries. This article supports the claims, already made by other scholars working in the field, that prototype theory may greatly augment our understanding of legal (i.e. statutory, judicial) interpretation. Legal provisions are traditionally written as classical definitions, but they are rarely applied that way. Statutory concepts tend to be interpreted with a great deal of flexibility, using a wide array of extra-textual factors. This is especially true for the case law of the Court of Justice of the European Union, which has to deal with the challenges of the multilingual, supranational law of the European Union.